Studi Komparasi Penggunaan Strategi Tebak Kata Dan Scramble Terhadap Hasil Belajar Ipa Siswa Kelas Iv Sd Muhammadiyah 3 Surakarta Tahun 2015/2016 - PRATIWI HADIYATI, INTAN (2016)
This study aims to determine: (1) the difference between the use of strategies of guess the word with the strategy scramble for learning outcomes IPA fourth grade students of SD Muhammadiyah 3 Surakarta, (2) a better strategy between strategy guess the word with the strategy scramble in science teaching to the results students of class IV 3 SD Muhammadiyah Surakarta. This study was an experimental study. Subjects in this study were students IVA and IVB 3 SD Muhammadiyah Surakarta in 2015/2016. Data collection techniques used are observation, documentation and testing. The analysis technique used is preceded by the t-test analysis prerequisite test is a test of balance and normality test. Based on the results of data analysis with a significance level of 5% obtained t > t table, namely 2.182> 1.990 with an average value of learning outcomes thematic IVB class higher than the class IVA, namely 82.92> 78.47. The conclusion of this study are as follows: (1) there is a difference between using a strategy of guess the word with the strategy scramble for learning outcomes IPA fourth grade students of SD Muhammadiyah 3 Surakarta, (2) strategy scramble better the learning outcomes of science students in comparison with the strategy of guess the word. Keyword: learning outcomes, comparative studies, scramble, guess the word